Coordinated changes in glycosylation regulate the germinal center through CD22 - Enterina, Jhon R.; Sarkar, Susmita; Streith, Laura; Jung, Jaesoo; Arlian, Britni M.; Meyer, Sarah Johanna; Takematsu, Hiromu; Xiao, Changchun; Baldwin, Troy A.; Nitschke, Lars; Shlomchick, Mark J.; Paulson, James C.; et al. (Cell Reports, 2022)
Germinal centers (GCs) are essential for antibody affinity maturation. GC B cells have a unique repertoire of cell surface glycans compared with naive B cells, yet functional roles for changes in glycosylation in the GC have yet to be ascribed. Detection of GCs by the antibody GL7 reflects a downregulation in ligands for CD22, an inhibitory co-receptor of the B cell receptor. To test a functional role for downregulation of CD22 ligands in the GC, we generate a mouse model that maintains CD22 ligands on GC B cells. With this model, we demonstrate that glycan remodeling plays a critical role in the maintenance of B cells in the GC. Sustained expression of CD22 ligands induces higher levels of apoptosis in GC B cells, reduces memory B cell and plasma cell output, and delays affinity maturation of antibodies. These defects are CD22 dependent, demonstrating that downregulation of CD22 ligands on B cells plays a critical function in the GC.
CRIS-Team Scopus Importer:2022-04-01
Keywords: antibodies; B cell receptor; CD22; germinal center; GL7; glycosylation; Siglec